Pengaruh Pemberian Madu Terhadap Peningkatan Stamina, Daya Tahan Otot Lengan, dan Kadar Asam Laktat pada Atlet Bulutangkis di Club Jaya Pratama Bandung - Hilmi Najib Rijaldi; Reshandi Nugraha; Teten Hidayat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of honey administration on increasing stamina, arm muscle endurance, and lactic acid levels in badminton athletes from Club Jaya Pratama Bandung. The study used a quasi-experimental method with a pretest-posttest control group design. The study sample consisted of 20 athletes divided into an experimental group and a control group of 10 individuals each. The experimental group was given 70 grams of honey dissolved in 250 ml of water and consumed 30–60 minutes before training for 16 sessions, while the control group underwent training without honey. The research instruments included the Arm Curl Test to measure arm muscle endurance, the Bleep Test to measure VO₂Max as an indicator of stamina, and Accutrend Lactate to measure lactic acid levels. Data analysis was performed using the Shapiro-Wilk normality test, Levene's homogeneity test, Paired Samples t-test, and Independent Samples t-test. The results showed a significant increase between the pre-test and post-test in all variables in both the experimental and control groups (p<0.05). However, the Independent Samples t-Test results showed no significant differences between the experimental and control groups in right arm muscle endurance (p=0.063), left arm muscle endurance (p=0.877), VO₂Max (p=0.718), and lactic acid levels (p=0.905). Therefore, honey supplementation has not been proven to be more effective than regular exercise in increasing stamina, arm muscle endurance, and reducing lactic acid levels in badminton athletes. Keywords: Lactic Acid, Badminton, Arm Muscle Endurance, Honey, Stamina